A Herderian Perspective on Finland, Sibelius, and the Kalevala - Philip R. Cataldo (Musical Offerings, 2023)
Situated amidst the revolutionary spirits of 19th-century Europe, Finnish nationalists sought to bring an end to roughly half a millennium of foreign rule for their land and their people. According to the German philosopher Johann Gottfried Herder, a community must have a common language and a common history in order to constitute a nation. At this time, Finland had neither. Although Herder’s political philosophy is considered crucial to understanding the nationalist movements that took place in Europe during this period, Finland’s peculiar success in attaining and sustaining independence has until this point remained unexplained relative to a Herderian framework. This study consists primarily of a distillation of Herder’s philosophy and an investigation of Finland’s history, with a particular focus on the music of the composer Jean Sibelius and the Kalevala, a collection of Finnish mythological stories. The findings of this investigation suggest that the emergence of the Finnish nation can be understood within a Herderian framework because the music of Sibelius and the Kalevala fulfilled the roles of a common language and common history. This provides a more nuanced understanding of both Herder’s philosophy and the relationship between music and language.